Attitudes toward Genetic Testing for Hypertension among African American Women and Girls - Jacquelyn Y. Taylor; Bronwen Peternell; Jennifer A. Smith (Nursing Research and Practice)
Introduction. Although African American (AA) women have the highest prevalence of hypertension and many genetic studies have been conducted to examine this disparity, no published studies have investigated their attitudes toward genetic testing for hypertension. The purpose of the present study was to use the health belief model as a guide to examine attitudes toward perceived barriers and benefits of genetic testing held by AA multigenerational triads and to determine whether they differed by generation, age, education, or income level. Methods. A descriptive correlational research design were used with 183 African American women and girls from Detroit. Correlations between triad membership, age, income, and education level were examined for association with attitudes toward genetic testing. Results. Increasing age and education were associated with significant differences in attitudes regarding benefits (F[2,160]=5.19, P=0.007, d=0.06) and awareness (F[2,160]=6.49, P=0.002, d=0.08). No statistically significant differences existed on the three subscales when compared by income levels or triad membership. Conclusions. This highlights the need for increased outreach to younger generations regarding benefits of genetic services. Further research is necessary to determine whether rural and male populations have similar beliefs.